Pembelajaran Literasi dalam Gerakan Literasi Sekolah (GLS) dan Penguatan Pendidikan Karakter (PPK) di SMP Kota Malang - Yuni Pantiwati; Fendy Hardian Permana; Tuti Kusniarti (Universitas Sebelas Maret, 2019)
The results of the PISA and TIMSS studies show that student literacy in Indonesia is still low. Low literacy is caused by many factors, one of which is the learning process. The learning process in class must be really designed in the form of literacy learning. The government in overcoming this issue launched the School Literacy Movement (GLS) and Character Education Strengthening (PPK). GLS has three stages, namely habituation, development, and learning. PPK aims to develop student character where there are 5 main values of character, namely religious, nationalist, independent, mutual cooperation, and integrity. Based on this, it is necessary to integrate literacy learning in GLS and PPK. The purpose of the study was to know the implementation of literacy learning in GLS and PPK. This type of research is descriptive with a qualitative approach through FGD to Principals, Middle School Science Teachers, and Malang City Middle School MGMP administrators. Quality descriptive data analysis using the Milles and Huberman models. The results showed that the use of strategies and approaches to teaching and learning is still not effective in developing literacy, literacy has not been optimal in developing thinking skills, difficulties in integrating PPK, school literacy ecosystems have not fully developed a school literacy culture, the need for increased collaboration in the GLS program